A representação do jovem contemporâneo na obra 100 mil seguidores, de Luis Dill - Silva, Sandremir Claudiano da (2024)
Youth literature is conceptualized as a set of literary texts that are written especially for teenage readers, taking into account their needs, interests and characteristics, addressing topics relevant to teenagers, such as identity, sexuality, family, friendship, school, among others. It is an art form that can move and sensitize readers, leading them to reflect on their own lives and the world around them. From this perspective, the writer Luis Dill presents themes in the plot of his works that portray all the problems faced by this generation. In this way, the present research aims to investigate in the work 100 thousand followers (2019), the research corpus, the occurrences of social and urban violence in fiction and the attempts to emulate the digital in the printed work to verify whether these literary resources help in the formation of aesthetic reader. Furthermore, the analysis of the work deals with the behavior of contemporary young people, reflecting their anxieties, confrontations, social isolation and discussing taboo topics such as self-mutilation and suicide. The research has an exploratory and bibliographical perspective, with qualitative analysis of an interpretative nature, in order to understand the production processes of the work and the connections that are constituted in the elaboration process. The analysis begins through State of the Art studies, after surveying Luis Dill’s critical fortune. Studies on Youth Literature will be based on research carried out by Regina Zilberman (2008), Lajolo and Zilberman (1984), João Luis Ceccantini (2000), Peter Hunt (2010), among others. About urban violence and social conflicts will be based on studies by researchers Eder Rodrigues Pereira (2000), Karl Eric Schollhammer (2007-2009), Regina Dalcastagnè (2003) and Lucrécia D‘Alessio Ferrara (1990), among others. The analysis of the characters is anchored in the studies of Antonio Candido (2011) with theoretical bases in his studies of the Character of the Novel. To discuss social relations in contemporary times, the contributions are made by the concepts of sociologist Zygmunt Bauman (2001;2004;2008). When promoting reflections on youth literature, focusing on the dramatizations of social and urban violence in fiction as a reflection of reality, the use of artistic and graphic resources in the composition of the books by Dill stands out, adapting to the demands of the publishing market.